Comprehensive Analysis of β-1,3-Glucanase Genes in Wolfberry and Their Implications in Pollen Development - Xin Zhang; Pinjie Zheng; Xurui Wen; Zhanlin Bei (Plants)
β-1,3-Glucanases (Glu) are key enzymes involved in plant defense and physiological processes through the hydrolysis of β-1,3-glucans. This study provides a comprehensive analysis of the β-1,3-glucanase gene family in wolfberry (Lycium barbarum), including their chromosomal distribution, evolutionary relationships, and expression profiles. A total of 58 Glu genes were identified, distributed across all 12 chromosomes. Evolutionary analysis revealed six distinct branches within wolfberry and nine distinct branches when compared with Arabidopsis thaliana. Expression analysis showed that 45 Glu genes were expressed in berries, with specific genes also being expressed in flowers and leaves. Notably, LbaGlu28 exhibited significant expression during the tetrad stage of pollen development and was localized in the cell wall. These findings provide valuable insights into the functional significance of Glu genes in wolfberry, highlighting their roles in development and their potential involvement in reproductive processes, particularly in pollen development.